Cultural Enculturization in the Art of Masks: A Case Study of the Industrial Enterprise of Batik Kayu, Bobung, Patuk, Gunung Kidul, Yogyakarta - Slamet Subiyantoro; Pujiyono Pujiyono; Kristiani Kristiani; Dwi Maryono; Yasin Surya Wijaya (Budapest International Research and Critics University, 2020)
This study aims to explore the process of enculturation of mask art with a case study in the wooden batik (batik Kayu) enterprise of Bobung Village, Patuk, Gunung Kidul, Yogyakarta. This study method uses a netnographic approach, which in principle is the same as classical ethnography, except that netnography uses the internet as a research media. The data were sourced from informants, places & events, and documents or archives. Data from informants were collected using in-depth online interviews. Place and event data were collected using online participatory observation techniques. In addition, the source documents or archives were collected using data analysis techniques or literature studies on relevant online data. The validity of the data was tested by using informant review techniques and source triangulation. Data were analyzed using flow techniques with data reduction, display, and verification procedures. The results of the study show that the process of enculturation or culture of mask art, both classic masks and creative masks (batik Kayu), is carried out informally (family environment), non-formal (community, UKM, and studio), and formal (learning in schools). This enculturation process is carried out from generation to generation, when the mask is still a classic mask (Panji mask) until the mask develops into a superior product with economic and tourism value as it is today (Creative Mask). The art of batik and classical masks has become the identity of the people of Bobung Village, Gunung Kidul, who have undergone changes in form, function and meaning during the enculturation process from previous generations to the next.